Cyclic Fatigue Resistance of Mtwo Rotary Instruments with two Different Instrumentation Techniques - Menezes, Silvio Emanuel Acioly Conrado; Batista, Shirley Machado; Magalhães, Diego Felipe Brandão de; Albuquerque, Diana Santana; Monteiro, Gabriela Queiroz de Melo (Iranian Endodontic Journal, 2019)
Introduction: The objective of this in vitro study was to evaluate whether cervical preparation with Mtwo files in a crown-down technique influences instrumentation time and the cyclic fatigue resistance of these instruments. Methods and Materials: Two instrumentation techniques were evaluated (manufacturer and crown-down). Each group consisted of 10 kits containing four Mtwo instruments (10/0.04, 15/0.05, 20/0.06, and 25/0.06), which were used to prepare three standard simulated curved resin canals. The mean instrumentation time and the corresponding number of cycles for each instrumentation (NCI) were recorded. The instruments were rotated at a constant speed of 300 rpm in a stainless-steel canal (diameter of 1.5 mm) at a 90° angle of curvature and 5-mm radius. The center of the curvature was 5 mm from the tip of the instrument. The cyclic fatigue resistance of the files was determined by counting the number of cycles to failure (NCF). Data were analyzed by the Mann-Whitney test. Results: The mean instrumentation time and NCI of files 10/0.04 and 15/0.05 were significantly lower (P<0.05) when the crown-down technique was used compared to the manufacturer’s method for the same tip size/taper file. There was no significant difference in the mean NCF between the two techniques. Conclusion: The crown-down technique did not interfere with resistance to cyclic fatigue. However, the shorter instrumentation time of files 10/0.04 and 15/0.05 could reduce the fracture risk in the case of reuse of these instruments. Keywords: Crown Down; Cycles to Failure; Cyclic Fatigue; Instrument Fracture; Root Canal Instrumentation